International trade and economic growth in open economies : the classical dynamics of Hume, Smith, Ricardo and Malthus - Berdell, John, 1960- (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 2002)
"In this book, John Berdell addresses the widely-held belief that classical economics distanced itself from policy issues and public debates regarding the effects of international trade on economic growth in advanced economies. He argues, through a detailed consideration of the evolution and structure of Hume's, Smith's, Ricardo's and Malthus' analyses, that it is not only contemporary international economic theory which takes account of these issues." "Berdell uses a series of non-linear dynamic models to illustrate and analyse important aspects of each author's discussion of the interactions between trade and growth. The findings are then extended to create a comparison of the classical models with recent empirical research in this area. Berdell suggests that John Stuart Mill's plan to synthesise and extend Hume's, Smith's and Ricardo's analysis of commercial society was rendered intractable by the limitations of Hume's associationalist psychology.".
"This work will be of great interest to both historians of economic ideas and economists concerned with modelling the interactions between growth and international trade."--BOOK JACKET.
1. Historical Dynamics: Cosmopolitan and International -- Pt. I. From Cosmopolitan to International: Four Classical Visions of Commercial Openness -- 2. Trading in Innovation: Hume and the Case for Freer Trade -- 3. Trading Animosity: Adam Smith and the Ambiguity of Nations -- 4. Stability and Openness: the Malthus-Ricardo Debate -- Pt. II. Some Classical Dynamics of Open Economy Growth -- 5. The Present Relevance of Hume's Open Economy Monetary Dynamics -- 6. A Dynamic Model of the Division of Labor and the Extent of the Market -- 7. Effective Demand and Technical Change in the Ricardo-Malthus Debate -- 8. Classical Political Economy: Back to Their Future?
Includes bibliographical references (p. 153-177) and index.
Keywords: International trade; Economic development; Classical school of economics